Rural Housing and Social Mobility: A District Level Study of PMAY-G in Tamil Nadu - Dr. N. RAMESHKUMAR; Mr. T. SATHISPRABU. M.A., M.Phil. SET., Ph.D; Mr. R. VENKATESH. M.A., Ph.D (PT. Radja Intercontinental Publishing, 2026)
Housing is a fundamental component of human development, contributing significantly to social security, economic stability, and overall quality of life. The Pradhan Mantri Awaas Yojana–Gramin (PMAY-G), launched by the Government of India in 2016, s eeks to provide pucca houses with basic amenities to all eligible rural households, thereby improving living standards and promoting inclusive rural development. This study examines the implementation and impact of PMAY-G at the district level in Tamil Nadu, with particular emphasis on its role in enhancing social mobility among rural beneficiaries. The research analyzes district-wise patterns of housing distribution, beneficiary selection, fund utilization, and completion rates, while assessing improvements in education, health, sanitation, employment opportunities, and social status resulting from access to secure housing. The study adopts a descriptive and analytical approach, utilizing secondary data obtained from government reports, census publications, PMAY-G dashboards, and district statistical handbooks. It also explores regional disparities in implementation and identifies the administrative, financial, and socio-economic factors influencing the scheme's effectiveness across districts. The findings indicate that PMAY-G has substantially improved housing conditions and access to essential services, contributing to greater socio-economic inclusion and upward social mobility among rural households. However, variations in implementation efficiency, delays in fund disbursement, and infrastructural challenges continue to affect outcomes in certain districts.